DELAYED TRAUMATIC INTRACRANIAL HAEMORRHAGES: A COMPARATIVE ANALYSIS OF CT SCAN & AUTOPSY FINDINGS - Chawla , Hitesh; Tyagi, Ashish; Yadav, Rohtas K; Gupta, Mohit (Journal of Forensic Medicine and Toxicology, 2021)
Context: In the current prevalent practice at trauma centers, axial non-contrast computerized tomography scan (CT scan) is the preferred diagnostic procedure in the traumatic head injury. In many patients, a CT scan might look normal, yet the patient may have a poor Glasgow Coma Scale and have an unfavourable outcome.